Age differences, proactive personality, coping strategies, job stress and job satisfaction among employees in outsourcing companies in Malaysia - Lai, Pei Wen (2019)
The job satisfaction in outsourcing industry is depleting globally due to its extensive job stress on employees, challenging environment and rapid economic growth. A study showed that employees in Malaysia only scored 17.8% on the very satisfied categories which infers that most of the employees in Malaysia are experiencing very low percentage of satisfaction as compared to neighbouring countries such as Singapore, Thailand and Indonesia. To date, the research on outsourcing industry is still limited in Malaysia. Proactive personality and coping strategies are known to have direct relationship with job stress and job satisfaction. Age differences is also an important factor in development psychology to study job satisfaction. Hence, the present study examines the job stress, proactive personality, coping strategies, age differences and job satisfaction among employees in outsourcing companies in Malaysia.